2016
DOI: 10.1177/1359105315624499
|View full text |Cite
|
Sign up to set email alerts
|

Type D personality: Application of DS14 French version in general and clinical populations

Abstract: The aim of this study was to validate the French-language version of the Type D personality scale-14 among general and clinical populations (acute coronary syndrome and breast cancer patients). The two-factor structure of the Type D personality scale-14 was confirmed by factorial and confirmatory analyses. Internal consistency for both subdimensions of Type D personality scale-14 (negative affectivity and social inhibition) was very good with α = .87 for each. Contrary to our expectations, the Type D prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
1
11
1
1
Order By: Relevance
“…Comparing age groups, in our study the Type D personality was the most prevalent in patients, aged 65-74 years, while in comparison group the peak was observed in the eldest group -people, aged 75 years and older. These results are inconsistent with the previous research, where the highest prevalence is mainly observed in young adults (33-38%) (Williams et al, 2008;Šmitas & Perminas, 2015;Batsele et al, 2017) and during the older age groups it transforms to a decreasing trend (e.g. Wiltink et al, 2011).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Comparing age groups, in our study the Type D personality was the most prevalent in patients, aged 65-74 years, while in comparison group the peak was observed in the eldest group -people, aged 75 years and older. These results are inconsistent with the previous research, where the highest prevalence is mainly observed in young adults (33-38%) (Williams et al, 2008;Šmitas & Perminas, 2015;Batsele et al, 2017) and during the older age groups it transforms to a decreasing trend (e.g. Wiltink et al, 2011).…”
Section: Discussioncontrasting
confidence: 57%
“…While individuals with high social inhibition scores have a tendency to perceive the environment as threatening that is commonly related with anhedonia (Lussier & Loas, 2015), social anxiety (Kupper & Denollet, 2014), depression and alexithymia (Batsele et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…the DS14 scale, may be beneficial in further studies. It may help diagnose, in a valid and reliable way, type D personality, and its 2 dimensions: negative emotionality and social inhibition [3,9,32].…”
Section: Discussionmentioning
confidence: 99%
“…Type D individuals are less likely to self-disclose and to share their medical symptoms with their doctors ( Schiffer et al, 2007 ), probably due to their discomfort with and distrust of others (SI). They are more alexythemic than non-D individuals ( Zohar et al, 2011 ; Batselé et al, 2016 ). However, they are awash with negative affectivity (NA), especially moodiness and irritability.…”
Section: Introductionmentioning
confidence: 99%